Corrigendum to: Characterization of Industrial Pt-Sn/Al2O3 Catalyst and Transient Product Formations during Propane Dehydrogenation [8(1), (2013), 77-82] (Bulletin of Chemical Reaction Engineering & Catalysis, 2014)
Corrigendum to: Kah, S.H., Joanna Jo, E.C., Sim, Y.C., Chin, K.C. (2013). Bulletin of Chemical Reaction Engineering & Catalysis, 8(1): 77-82. (doi:10.9767/bcrec.8.1.4569.77-82). In Abstract, typed as: “….. Due to information paucity, the physicochemical characteristics of the commercially obtained regener-ated Pt-Sn/Al2O3 catalyst (operated in moving bed reactor) and coke formation at different tempera-tures of reaction were discussed…..”In the Abstract, the phrase of “(operated in moving bed reactor)” should be deleted.Erratum: Kah, S.H., Joanna Jo, E.C., Sim, Y.C., Chin, K.C. (2013). Bulletin of Chemical Reaction Engineering & Catalysis, 8(1): 77-82. (doi:10.9767/bcrec.8.1.4569.77-82).In Abstract section, the phrase of “(operated in moving bed reactor)” was deleted.Therefore, the sentence in the Abstract was corrected to: “….. Due to information paucity, the physico-chemical characteristics of the commercially obtained regenerated Pt-Sn/Al2O3 catalyst and coke for-mation at different temperatures of reaction were discussed…..”.© 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)